THEORIES OF FUNDAMENTAL RIGHTS AND THEIR IMPACT ON THE INTERPRETATION OF THE CONSTITUTION - Adam JAKUSZEWICZ (Zeszyty Naukowe Wyższej Szkoły Finansów i Prawa w Bielsku-Białej, 2014)
Constitutional provisions stipulating the fundamental rights are to a great extent of an indefinite character. That is why their interpretation consists in their concretization, i.e. of their filling with normative substance. Since this cannot be done solely by means of traditional methods, an interpreter resorts to a theory of fundamental rights, which has a decisive impact on the outcome of the interpretation. The article discusses the most influential theories of fundamental rights and analyzes their implications for the interpretation of the constitution. Furthermore, the author indicates the need to draw up a theory of fundamental rights proper to the constitution in force, i.e. inferred from its provisions, that would be binding on an interpreter.